Funkcjonalność narzędzi do monitorowania stacji roboczych sieci lokalnych - Mazur, Hanna; Mazur, Zygmunt; Mendyk-Krajewska, Teresa (The functionality of the tools for monitoring local network workstations, 2006)
Increasingly more employees of companies and entrepreneurships use computers and the Internet in their daily work. At the same time there are more and more tools on the market that allow to monitor their workstations and manage their access to Internet services. Employers make a decision to deploy such products because of different reasons, the most important of which is the increase of company data's security and work efficiency. In the paper we have investigated the basic possibilities of available products for workstation monitoring and the issues related to their use.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 108-115